29.2k views
2 votes
Please show work! Thank you!

Please show work! Thank you!-example-1
User Blkpingu
by
5.9k points

1 Answer

6 votes

Answer:

Explanation:

21)

The sine rule is expressed as

a/SinA = b/SinB = c/SinC

Where a, b and c are the length of each side of the triangle and angle A, Angle B and angle C are the corresponding angles of the triangle. Therefore,

12/Sin 64 = x/Sin 12

Cross multiplying, it becomes

xSin 64 = 12Sin12

xSin 64 = 12 × 0.209

0.8988x = 2.508

x = 2.508/0.8988

x = 2.79

The sum of the angles in a triangle is 180 degrees. Therefore, the unknown angle in triangle is

180 - (64 + 12) = 104 degrees. Therefore,

y/Sin104 = 12/Sin64

ySin64 = 12Sin104

0.8988y = 12 × 0.9703 = 11.6436

y = 11.6436/0.8988

y = 12.95

22) we would apply the law of Cosines which is expressed as

a² = b² + c² - 2bcCosA

Therefore,

28² = 20² + 24² - 2 × 20 × 24Cosx

784 = 400 + 576 - 960Cosx

784 = 976 - 960Cosx

960Cosx = 976 - 784 = 192

Cosx = 192/960 = 0.2

x = Cos^(-1)0.2

x = 78.5°

User Vanekjar
by
5.8k points